2015
DOI: 10.5155/eurjchem.6.4.381-386.1296
|View full text |Cite
|
Sign up to set email alerts
|

Purity assessment and determination of sertaconazole in bulk and pharmaceutical formulations based on spectrophotometric and chromatographic approaches

Abstract: Stability evaluation of the drug substance is an integral part of the systematic approach to stability studies. Hence, three simple, sensitive and precise methods depending on two different techniques as UV spectrophotometry and chromatography were adopted for the task of stability indicating determination of sertaconazole (SER) in presence of its acidic degradation products. The first method is Zero-crossing first derivative ( 1 D) spectrophotometric one, which allows the determination of SER over a concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 7 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…Statistical analysis of the results obtained by the proposed method and the reported method [39] was performed and the results are listed in Table 4. It was found that the calculated tand F-values were less than the theoretical ones [45,46], indicating no significant differences between the proposed method and the reported one.…”
Section: Discussionmentioning
confidence: 96%
“…Statistical analysis of the results obtained by the proposed method and the reported method [39] was performed and the results are listed in Table 4. It was found that the calculated tand F-values were less than the theoretical ones [45,46], indicating no significant differences between the proposed method and the reported one.…”
Section: Discussionmentioning
confidence: 96%